Recent development in the application of bulk metallic glasses. (20th December 2022) - Gao, K.; Zhu, X.G.; Chen, L.; Li, W.H.; Xu, X.; Pan, B.T.; Li, W.R.; Zhou, W.H.; Li, L.; Huang, W.; Li, Y.
Highlights: Recent development in the application of BMGs is introduced. The advantages of BMGs processes are discussed with other processing techniques. An outlook for the future directions of BMGs is put forward. Abstract: Over the past decades, considerable efforts have been made in the commercial application of bulk metallic glasses (BMGs). Despite great challenges faced by the industrial players, significant progress has been achieved, and millions of commercial products for various kinds of applications have been shipped around the world. Here in this paper, we shall present the alloys suitable for the actual products in the application and discuss the merits of the processing technique of BMGs over the existing processing techniques and materials. Most importantly we demonstrate the typical examples of products over the past few years. Finally, future directions of the industrialization of BMGs are also discussed.